EFFECTIVE METHODS OF MANAGING STUDENTS’ COGNITIVE LOAD IN THE PROCESS OF TEACHING INFORMATION TECHNOLOGIES (Eureka Journal of Health Sciences & Medical Innovation, 2026)
This study is aimed at identifying and improving effective methods for managing students’ cognitive load in the process of teaching information technologies. During the research, the main principles of Cognitive Load Theory were analyzed, and methods focused on optimal presentation of educational materials, information segmentation, rational use of multimedia tools, and reduction of excessive cognitive load were developed. The practical experiment was conducted at Andijan State Medical Institute with the participation of 60 students. The obtained results demonstrated that an approach based on cognitive load management increases students’ level of knowledge acquisition and ensures the effectiveness of the educational process. The findings of the research are of significant importance for improving the methodology of teaching information technologies in medical higher education institutions.
Keywords: Information technologies, cognitive load, cognitive load theory, teaching methodology, multimedia tools, segmentation, educational process, knowledge acquisition, educational efficiency, medical education, innovative approach, didactic design, interactive learning, digital educational technologies, student activity.